Information Disclosure on Fixed Assets in Non-Financial Reporting in the Mechanical Engineering Industry - I. V. Alekseeva; E. Yu. Andryushchenko (Учёт. Анализ. Аудит)
The information about fixed assets is crucial for users to understand the operations of commercial organizations, as these assets play a vital role in their activities. The required information about fixed assets is incomplete in organizations’ financial statements. Commercial companies in the Russian mechanical engineering industry, in particular, rely heavily on fixed assets, making up over half of all property-related fixed assets. The study’s objective is to research information about fixed assets in non-financial reports of mechanical engineering organizations. The methodological base includes the theory of accounting and making accounting for financial and non-financial reporting in digitalization. The research focuses on the theoretical framework and methods involved in disclosing information about fixed assets in non-financial reports. The paper provides a comparative analysis of annual reports of organizations in the mechanical engineering industry: their structure, composition and content, classification of fixed assets. The authors proposed a grouping of indicators for evaluating fixed asset efficiency and compiled a list of the most relevant. This research contributes both theoretically and practically by presenting a recommended template for non-financial reporting on intangible assets specifically tailored to organizations in the mechanical engineering field. This will empower interested users to make effective choices in managing fixed assets. The study’s results are useful for mechanical engineering firms that prioritize transparently sharing non-financial information with interested audiences. This research offers valuable theoretical frameworks and practical recommendations for both academics and professionals working on the presentation of financial and non-financial information about fixed assets.